CORRELAÇÕES E ANÁLISE DE TRILHA EM MAMONA CONSORCIADA COM GERGELIM, ALGODÃO, MILHO E FEIJÃO CAUPI - Pinto, Ciro de Miranda; Sizenando Filho, Francisco Aires; Oliveira Pinto, Olienaide Ribeiro de; Batista Cysne, Junior Regis; Pitombeira, João Bosco (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2011)